Financial Reporting Quality and Investment Decisions Making in Organizations: An Empirical Analysis of Selected Listed Manufacturing Firms in Nigeria - Adeyinka Damilola Ojomo (ORGANIZE: Journal of Economics, Management and Finance, 2024)
The study examined the effect of financial reporting quality on investment decisions in ten listed manufacturing firms in Nigeria. The study used data from annual financial statements published between the period of 2013 to 2022. Also, unit root testing and co-integration were used as the pre-test technique; while, panel data, fixed effect result, random result, fixed effect result and Hausman’ test were applied for the formulated objectives. The Levin, Lin & Chut, Im, Pesaran and Shin W-stat and ADF - Fisher Chi- unit root techniques demonstrated that return on investment, accounting conservation, timely loss recognition and earning quality were integrated at order one and at level. Kao co-integration technique test confirmed a long-term association between the variables. Hence, indicating a long-term connection between return on investment, earning quality and accounting conservation, timely loss recognition. Also, the outcome indicates that the Hausman's test probability value was greater than 0.05 (p>0.05) levels of significance, indicating that Random effect estimate is the best estimator to explain the result. The result from the Random technique showed that earning quality and accounting conservation were significant at 5% significant level and directly related to return on investment; while, timely loss recognition was positively related to return on investment but non-significant at 5%. This suggests that 1% increase in earning quality (EAQ) and accounting conservation brought about 5.2% and 0.9% increase in return on investment (ROI) respectively; while, timely loss recognition had zero effective on return on investment (ROI). The study concluded that financial reporting quality boosts investment decisions made by investors, which promotes the rate of return on investments in listed manufacturing corporation.  It is recommended that management of manufacturing organization should ensure that their respective financial reporting provide valuable knowledge for decision-making, with respect to the standard of financial statements through complying within commonly agreed accounting standards.